Analysis of the Success and Acceptance of ERP SAP Implementation Using an Integrated UTAUT3 and DeLone & McLean (D&M) Model at PT Semen Padang - Yanuardi; Vera Pujiani; Alfitman (LP2M IAIN Palopo, 2026)
This study aims to analyze the determinants of User Satisfaction and its influence on Net Benefit in the implementation of SAP ERP at PT Semen Padang. The research model integrates UTAUT3 (Performance Expectancy, Effort Expectancy, Social Influence, Facilitating Condition) with the DeLone & McLean IS Success Model (Information Quality, System Quality). A quantitative approach was applied using a Likert-scale survey distributed to 251 active SAP users from various job levels, with data analyzed using Structural Equation Modeling (SEM) based on Confirmatory Factor Analysis (CFA) in AMOS. The results indicate that Performance Expectancy (β = 0.256; p < 0.001), Effort Expectancy (β = 0.357; p < 0.001), Facilitating Condition (β = 0.189; p = 0.006), Information Quality (β = 0.262; p < 0.001), and System Quality (β = 0.179; p = 0.009) have a significantly positive effect on User Satisfaction, whereas Social Influence (β = 0.055; p = 0.410) is not significant. Furthermore, User Satisfaction shows a significant positive influence on Net Benefit (β = 0.183; p = 0.020). The structural model demonstrates a good level of model fit across multiple goodness-of-fit indices and model stability based on Hoelter’s Critical N. These findings confirm that expected performance, ease of use, technical support conditions, and both information and system quality are key determinants of User Satisfaction. The practical implications encourage the organization to continuously improve system and information quality, strengthen technical support, and enhance user competency to maximize the value of SAP ERP in supporting operational performance and strategic decision-making at PT Semen Padang.